HEPATOPROTECTIVE EFFECT OF Physalis angulata L. LEAF ETHANOL EXTRACT AGAINST BUSULFAN-INDUCED LIVER DAMAGE IN FEMALE RATS - Elsi Rahmadhani; Aryani Sismin Satyaningtijas; Damiana Rita Ekastuti; Ronald Tarigan; I Ketut Mudite Adnyane; Kusdiantoro Mohamad; Wahono Esthi Prasetyaningtyas; Yanti Sulistyana (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTSBusulfan can damage the liver by triggering oxidative stress Physalis angulata leaves show natural liver protective effects Extract reduced oxidative damage in liver tissue Liver structure improved after extract treatment Early treatment provided stronger liver protection than delayed useABSTRACTLiver disease is the leading cause of death worldwide, with drug-induced hepatotoxicity representing a major contributing factor. Busulfan, an anticancer drug used in chronic myeloid leukemia, is cytotoxic to proliferating cells and can induce liver injury. Physalis angulata L. (ground cherry) contains bioactive compounds with potential hepatoprotective properties. This study aimed to evaluate the protective effects of ethanol extract of Phyasalis angulata L. (EEPA) leaves on busulfan-induced liver damage in female Sprague–Dawley rats. Twenty-five rats were randomly divided into five groups: P1 (normal control), P2 (busulfan 40 mg/kg BW, single dose), P3 (extract 300 mg/kg BW, days 1–28), P4 (busulfan + extract, days 1–28), and P5 (busulfan + extract, days 14–28). Parameters assessed were alanine aminotransferase (ALT) and aspartate aminotransferase (AST), the level of malondialdehyde (MDA) in liver, and liver histology. Data were analyzed using one-way analysis of variance (ANOVA) followed by a post hoc test. The results showed that Physalis angulata L. extract did not cause significant differences in the serum ALT and AST levels but significantly reduced the MDA concentrations and improved the liver histological architecture. Busulfan administration significantly decreased hepatocyte count and increased Kupffer and inflammatory cells, fatty degeneration, and necrosis. Early administration of the extract (P4) demonstrated stronger hepatoprotective effects compared with delayed administration (P5). These findings suggest that EEPA leaves exerts hepatoprotective effects against busulfan-induced liver injury in rats, likely through antioxidant activity, as evidenced by subsequent histological improvement, and highlighting its potential as a natural hepatoprotective agent.